The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/app.50201
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized poly (2,6‐dimethyl‐1,4‐phenylene oxide) crosslinked by tertiary amine and siloxane for anion exchange membranes

Abstract: A series of tertiary amine and siloxane crosslinked composite anion exchange membranes were prepared by incorporating 2‐(3,4‐epoxycyclohexyl) ethyltrimethoxysilane (EHTMS) and N,N,N′,N′‐Tetramethyl‐1,6‐hexanediamine (TMHDA) into N‐Methyldiethanolamine (MDEA)‐functionalized poly (2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) backbone via sol‐gel process. The resultant membranes named as AEM‐X (X = 1, 2, 3, 4), which own a three‐dimensional (3D) cross‐linking structure, exhibit superior swelling resistance, mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…According to scientific reports 9,23 , this issue can be attributed to the inability of AEMs to manage and maintain a uniform hydrophilic pathway inside the membranes during the service life. Among them, polyphenylene oxide (PPO) based polymers functionalized by trimethylammonium quaternary groups and their derivatives showed high alkaline stability and great ion transport properties, making them a promising candidate in fuel cell applications [24][25][26][27] . Also, recent studies have shown that PPO backbone tethered with long flexible alkyl chains (more than four carbon units) as a spacer or extenders bound to the cationic pendant group have better structural integrity and ion transport properties as compared to those without alkyl sidechains [28][29][30][31][32][33][34][35] , while the underlying mechanisms remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to scientific reports 9,23 , this issue can be attributed to the inability of AEMs to manage and maintain a uniform hydrophilic pathway inside the membranes during the service life. Among them, polyphenylene oxide (PPO) based polymers functionalized by trimethylammonium quaternary groups and their derivatives showed high alkaline stability and great ion transport properties, making them a promising candidate in fuel cell applications [24][25][26][27] . Also, recent studies have shown that PPO backbone tethered with long flexible alkyl chains (more than four carbon units) as a spacer or extenders bound to the cationic pendant group have better structural integrity and ion transport properties as compared to those without alkyl sidechains [28][29][30][31][32][33][34][35] , while the underlying mechanisms remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some chemically modified PPO type polymers have been studied for AEMs, and they usually possessed excellent membrane-forming ability and enough mechnical strength. 4,32 In this work, we designed and fabricated a novel blend system comprising of a linear brominated PPO and a hyperbranched HVBC. The highly conductive and mechanically stable cross-linked networks with a loose "linear-hyperbranched" PPO-HVBC structure was expected to be constructed after the essential steps of cross-linking, quaternization and hydroxylation.…”
Section: Fabrications Of the Cross-linked Blend Membranes Containing ...mentioning
confidence: 99%
“…As a vital component of AEMFCs, anion exchange membranes (AEMs) play a crucial role in isolating gases and transporting ions. 4,5 Generally, AEMs are casted from the polymer electrolytes, which are usually composed of a polymer skeleton, mobile anions and functional cationic groups. [6][7][8] So far, a variety of polymers, including aromatic polymers (eg, polysulfones, polyetherketones, polyphenylene ethers, polybenzimidazoles, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous uses of two cross-linking agents were intended to improve the dimensional stability and alkali resistance of the membrane and to maintain a good hydroxide conductivity, which reached 21 mS/cm at 80 °C. The alkaline stability displayed a moderate improvement [ 86 ]. Another approach based on BrPPO was exploited by He et al [ 87 ].…”
Section: Membranes For Electrochemical Energymentioning
confidence: 99%